Psycholinguistic Specifics of Understanding by Ukrainian Students the Principles of Nomination of Linguocultural Models “clothing” in English and Ukrainian - Наталія Михальчук; Павло Левчук; Ернест Івашкевич; Людмила Ясногурська; Олена Чернякова (Психолінгвістика)
The purpose of the article is: to show psycholinguistic peculiarities of understanding by Ukrainian students the principles of nomination of linguocultural models “clothing” in the English and Ukrainian languages.